Pengaruh Pengelolaan Kelas di Sekolah - Salsabila Nasution; Neviyarni S (Universitas Negeri Padang, 2022)
Classroom management is a teacher's skill in order to create a pleasant learning atmosphere, and can control it if there are disturbances during learning. The aim of this research is to find out how much influence the classroom management has on students by the teacher. This research also aims to compare the effects of classroom management that have the greatest impact on students. The method in this research is a literature study by collecting library data from several sources of scientific research in accordance with classroom management from 2017-2022. The results of a literature study conducted by researchers related to the effect of classroom management on students at school can be concluded that classroom management is very influential for several aspects of student learning including student learning motivation, student achievement, student learning outcomes, student understanding, student activity, and attitudes student. Among the several aspects that are affected by classroom management, learning achievement is very dominant and has been found and carried out by many people. Keywords: Influence, Classroom management, Teachers, students